Management of physical child abuse in South Africa: literature review and children's hospital data analysis. (1st November 2013) - Janssen, T L; van Dijk, M; Al Malki, I; van As, A B
Abstract : Background : The reason for this review is the lack of data on the management of physical abused children in Africa. The primary goal of the first part is to outline the management of physical child abuse in (South) Africa and provide suggestions for other governments in Africa on which to base their management of physical child abuse, at both governmental and hospital management level. The main aim of the second part is to outline the extent of the problem as seen at the Red Cross Memorial Children's Hospital (RCH) in Cape Town. Material and Methods: The National Library of Medicine's PubMed database was searched for articles specifically about the management of physical child abuse. Hospital data were analysed in two phases: one addressed various types of assault in order to assess the number of patients admitted to the trauma unit of RCH between 1991 and 2009, and the other to identify all children with suspected non-accidental injury (NAI) presenting to the trauma unit at RCH from January 2008 until December 2010. Results : Information on physical abuse of children in Africa in the English scientific literature remains disappointing with only two articles focusing on its management. RCH data for the period 1991-2009 recorded a total number of 6415 children hospitalised with injuries following assault, who accounted for 4·2% of all trauma admissions. Types of abuse included assault with a blunt or sharp instrument, rape/sexual assault and human bite wounds. Over the last 2 decades, there has been a minor decline in the number of cases of severe abuse requiring admission; admissions for other injuries have remained stable. More detailed analysis of hospital data for 2008-2010, found that boys were far more commonly assaulted than girls (70·5% vs 29·5%). Physical abuse appeared to be the most common cause of abuse; 89·9% of all boys and 60·5% of all girls presented after physical abuse. Conclusion : In order to eradicate child abuse, awareness of it has to be promoted in the community at large. Because the types of child abuse vary between countries, each requires its own research in order to develop a policy tailored to their particular requirements. In summary, an increased focus on the prevention of violence against children is urgently needed in order to curb the increasing trend of assaults on children. As the causes and risk factors for violence against children vary, multi-disciplinary and multi-sectoral co-operation and collaboration will be required. It is hoped that this report will help raise awareness among health-care practitioners of NAI and its complexities.